The example of a Jewellery retail family firm: How they overcome COVID-19 with innovation. - Soler-Porta, Mariano; Rodríguez-Díaz, Beatriz (My University, 2024)
Innovation is a popular topic in many fields, but it holds a special significance when it comes to family businesses due to their unique decision-making processes. Additionally, there is a lack of research on how family-owned companies can use innovation to overcome economic crises This paper presents a case study of a family-owned jew-ellery retail business and how they navigated the COVID-19 crisis through innovation. This is an understudied sector in the literature and the results obtained by the business will serve as a basis for further research.
Keywords: Joyerías - Innovaciones; Pandemia de la Covid-19, 2020- - Aspectos económicos; Empresas familiares; Jewellery sector; Family firms; Innovation; Covid-19